2021
DOI: 10.3390/agriculture11111140
|View full text |Cite
|
Sign up to set email alerts
|

Study on Plant Growth and Nutrient Uptake under Different Aeration Intensity in Hydroponics with the Application of Particle Image Velocimetry

Abstract: Aeration is considered beneficial for hydroponics. However, little information is available on the effects of aeration, and even less on solutions that use bubble flow and their agronomic effects. In this study, the effects of aeration intensity on plants were studied through cultivation experiments and flow field visualization. It was found that the growth of plants did not increase linearly with an increase in aeration intensity. From the results of this study, when the aeration intensity was within the low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…Although the metabolites of the roots grown under different flow conditions showed differential changes after approximately 7 d of treatment, it may take some time until these differences are translated into the phenotype. Additionally, we found that plants exhibited poorer growth when exposed to a high-flow environment, which is consistent with the conclusions of Baiyin et al [4][5][6].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the metabolites of the roots grown under different flow conditions showed differential changes after approximately 7 d of treatment, it may take some time until these differences are translated into the phenotype. Additionally, we found that plants exhibited poorer growth when exposed to a high-flow environment, which is consistent with the conclusions of Baiyin et al [4][5][6].…”
Section: Discussionsupporting
confidence: 93%
“…The main difference between hydroponics and soil-or substrate-based cultivation is that hydroponics uses a flowing medium, like nutrient solution, as the cultivation substrate. This nutrient solution offers several unique advantages [4]. First, it promotes the circulation and even distribution of nutrient ions within the cultivation system and can deliver nutrient ions to plant roots via the circulation system, thereby preventing the formation of nutrientdepleted zones and ensuring an adequate nutrient supply to roots.…”
Section: Introductionmentioning
confidence: 99%
“…The main plant component responsible for nitrogen uptake is the roots (Baiyin et al., 2021). These nutrients are available to plants and required in appropriate amounts.…”
Section: Resultsmentioning
confidence: 99%
“…Of note is that PFOA likely partitioned to the air–water interface, meaning that a thin layer of higher‐concentration PFOA existed at the top of the hydroponic solution (Costanza et al., 2019). Our system was aerated to oxygenate, agitate, and homogenize nutrients in the solution (Baiyin et al., 2021; Silva et al., 2019), but we hypothesize that the upward movement of the air bubbles exacerbated the tendency of PFOA to partition at the air–water interface. With the measured concentration in the bulk nutrient solution being lower than the overall PFOA concentration in the solution, the calculated BCFs in this work are conservative; hypothetical BCFs determined from a completely homogenized solution would be lower than those presented in this work (Figure 3).…”
Section: Resultsmentioning
confidence: 99%